2005
DOI: 10.1038/nsmb947
|View full text |Cite|
|
Sign up to set email alerts
|

A single amino acid residue can determine the sensitivity of SERCAs to artemisinins

Abstract: Artemisinins are the most important class of antimalarial drugs. They specifically inhibit PfATP6, a SERCA-type ATPase of Plasmodium falciparum. Here we show that a single amino acid in transmembrane segment 3 of SERCAs can determine susceptibility to artemisinin. An L263E replacement of a malarial by a mammalian residue abolishes inhibition by artemisinins. Introducing residues found in other Plasmodium spp. also modulates artemisinin sensitivity, suggesting that artemisinins interact with the thapsigargin-bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
210
3

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(226 citation statements)
references
References 19 publications
13
210
3
Order By: Relevance
“…The interaction of antimalarial artemisinin in P. falciparum was reported to occur through inhibition of PfATP6, a SERCA-type ATPase (Uhlemann et al 2005). Our data shows the ability of both antimalarial in modifying the calcium and proton dynamics in P. chabaudi internal stores (Fig.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The interaction of antimalarial artemisinin in P. falciparum was reported to occur through inhibition of PfATP6, a SERCA-type ATPase (Uhlemann et al 2005). Our data shows the ability of both antimalarial in modifying the calcium and proton dynamics in P. chabaudi internal stores (Fig.…”
Section: Discussionmentioning
confidence: 51%
“…Chloroquine is though to act by preventing the monomeric hemin from forming the inert and insoluble polymer hemozoin which is derived from digestion of hemoglobin in the acidic vacuole (Slater & Ceram 1992). Defining the sites of chloroquine action in Plasmodium, as well as determining how it is related to proton activity in the acidic compartment is of major importance in the physiology of these parasites.It has been reported that the antimalarial artemisinin act on PfATP6 (Ca 2+ ATPase) in P. falciparum, thus affecting Plasmodium Ca 2+ homeostasis (Uhlemann et al 2005).…”
mentioning
confidence: 99%
“…3 Initial laboratory studies have suggested that L263E substitution in PfATP6 affects the active site and induces conformational changes, reducing the affinity between the enzyme and artemisinin. 4 Subsequent studies carried out on field isolates have shown an association between increased 50% inhibitory concentration (IC 50 ) for artemether and either a single amino acid substitution S769N (in South American strains) or double amino acid substitutions E431K and A623E (in African strains). 5 Quiescence is another possible mechanism of resistance demonstrated in laboratoryadapted P. falciparum .…”
Section: Introductionmentioning
confidence: 99%
“…13 Amplification products were sequenced from the 5′-and 3′-ends by using an automated DNA sequencer (ABI Prism; Perkin Elmer Corp., Les Ulis, France) to determine the codons that were reported to be associated with artemisinin resistance (amino acid residues 263, 431, 623, and 769) and possible novel mutations in the pfatp6 gene. 4,5 On the basis of these studies, the wild-type haplotype was defined as LEAS. Known pfatp6 mutants include the West African double mutant type (E431K + A623E) and the South American single mutant type (S769N).…”
mentioning
confidence: 99%
“…Three-dimensional modelling and docking simulation demonstrated that artemisinin bound to SERCA by hydrophobic interactions leaving the peroxide bonds exposed and accessible to cleavage by iron, leading to enzyme inactivation and parasite death (Jung et al, 2005). This was supported by a single amino acid mutation (L263E) in parasite SERCA expressed in X. laevis oocytes that modulated sensitivity to artemisinin (Uhlemann et al, 2005) and by a single nucleotide polymorphism (S769N) associated to reduced in vitro artemether susceptibility in French Guiana isolates (Jambou et al, 2005). How this last mutation interferes with the artemether action remains unclear.…”
Section: Sarcoplasmic/endoplasmic Reticulum Calcium Pfatpase (Serca)mentioning
confidence: 99%